2016
DOI: 10.1155/2016/3417976
|View full text |Cite
|
Sign up to set email alerts
|

HBV Infection Status and the Risk of Cholangiocarcinoma in Asia: A Meta-Analysis

Abstract: Background. The inconsistent finding was between hepatitis B virus (HBV) infections and cholangiocarcinoma (CCA). This meta-analysis is to explore this relationship in Asia. Methods. A literature search was performed using PubMed, Web of Science, and Cochrane Library to October 30, 2015. Pooled incidence rate and OR with 95% CI were calculated using STATA 11.0. Results. Thirty-nine studies were included. The pooled incidence rate of CCA patients with HBV infection was 31% (95% CI 22%–39%). The pooled OR showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
0
30
0
2
Order By: Relevance
“…The association between HBV and iCCA has been also confirmed in another study, where an OR = 5.10 (95% CI 2.91‐8.95) was reported . More recently, a meta‐analysis including 39 studies reported an OR = 2.72 (95% CI 1.90‐3.88) for the risk of CCA in HBV positive patients; in particular, an OR = 3.184 (95% CI 2.356‐4.302) was found for iCCA, whereas a weak association was found for eCCA (OR = 1.407, 95% CI 0.925‐2.141) …”
Section: Risk Factorsmentioning
confidence: 55%
“…The association between HBV and iCCA has been also confirmed in another study, where an OR = 5.10 (95% CI 2.91‐8.95) was reported . More recently, a meta‐analysis including 39 studies reported an OR = 2.72 (95% CI 1.90‐3.88) for the risk of CCA in HBV positive patients; in particular, an OR = 3.184 (95% CI 2.356‐4.302) was found for iCCA, whereas a weak association was found for eCCA (OR = 1.407, 95% CI 0.925‐2.141) …”
Section: Risk Factorsmentioning
confidence: 55%
“…Asian countries) [79,80] . The range of the OR in the HbsAg positive subjects goes from 2.3 to 9.7 [ Table 1] [81] . The presence of cirrhosis increases the risk of CCA [ Table 1] even more by 2.5 fold (95% CI: 1.2-5.1; P = 0.02) in HBV, and 3.2 fold (95% CI: 1.231-8.148, P = 0.017) in HCV patients [41] .…”
Section: Multiple Risk Factors Reveal Icca Subtype-specific Pathogenesismentioning
confidence: 99%
“…The burden of HCV in the last decades has been associated with the specific increase of the iCCA as well as the HCC [81] . Accordingly, clinical and pathological observations suggested that liver cirrhosis is specifically Table 1.…”
Section: Multiple Risk Factors Reveal Icca Subtype-specific Pathogenesismentioning
confidence: 99%
“…HBV infection has been identified to be a risk factor for the incidence of ICC for a decade 9 - 11 . Subsequently, several studies have evaluated association between HBV infection and prognosis of ICC 12 - 19 .…”
Section: Discussionmentioning
confidence: 99%